Vermessung der Welt : Heterotopien und Wissenräume in der Kunst - Bucher Trantow, Katrin; Pakesch, Peter; Habsburg-Lothringen, Bettina; Huber, Hans Dieter; Krasny, Elke; Guttmann, Martin; Huemer, Katia; Ortner, Johanna; Kunsthaus Graz (Köln : Walther König, 2011)
Ackermann, Franz ; Weiwei, Ai ; Arztmann, Stefan ; Alighiero e Boetti ; Broodthaers, Marcel ; Buchner, Wolfgang ; Clegg & Guttmann ; Darboven, Hanne ; Dion, Mark ; Charles & Ray Eames ; Huber, Stephan ; Kogler, Peter ; et al.
Kunsthaus Graz, Universalmuseum Joanneum, Graz, 11. Juni - 4. September 2011.
kunstcatalogus